2.0 A X-ray structure of the ternary complex of 7,8-dihydro-6-hydroxymethylpterinpyrophosphokinase from Escherichia coli with ATP and a substrate analogue. - Stammers, D; Achari, A; Somers, DO; Bryant, P; Rosemond, J; Scott, D; Champness, J (1999)
The X-ray crystal structure of 7,8-dihydro-6-hydroxymethylpterinpyrophosphokinase (PPPK) in a ternary complex with ATP and a pterin analogue has been solved to 2.0 A resolution, giving, for the first time, detailed information of the PPPK/ATP intermolecular interactions and the accompanying conformational change. The first 100 residues of the 158 residue peptide contain a betaalpha betabeta alphabeta motif present in several other proteins including nucleoside diphosphate kinase. Comparative sequence examination of a wide range of prokaryotic and lower eukaryotic species confirms the conservation of the PPPK active site, indicating the value of this de novo folate biosynthesis pathway enzyme as a potential target for the development of novel broad-spectrum anti-infective agents.